Observation of a New Ξ−b Resonance; Physical Review Letters; Vol. 121, iss. 7 - Aaij R. Roel; Panshin G. L. Gennady Leonidovich; Strokov S. A. Sergey Aleksandrovich; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen